1982
DOI: 10.1002/aja.1001650302
|View full text |Cite
|
Sign up to set email alerts
|

Isolated guinea pig adrenocortical cells in vitro: Morphology and steroidogenesis in control and ACTH‐treated cultures

Abstract: Isolated guinea pig adrenocortical cells were maintained in long-term culture in order to perform sequential experiments on the same cell populations. The cells produced fluorogenic steroids, shown by thin-layer chromatography to be at least aldosterone, cortisol, and corticosterone. In addition, they increased production of these steroids when treated with either ACTH or dibutyryl cyclic AMP. Of particular interest was the fact that cultures treated for the initial 24-hour culture period with ACTH maintained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1985
1985
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 37 publications
(47 reference statements)
0
4
0
Order By: Relevance
“…The least-squares fit of the data points to a v against s hyperbola was used to calculate best-fit values of Vmax and Km, and results were reported as means ± SEM. Preparation of dispersed guinea pig fasciculatal glomerulosa cells Adult male guinea pigs (Hartley) weighing 850 grams were used for the preparation of primary cultures of fasciculata/glomerulosa (FG) cells, which were isolated using an adaptation of the procedure described by Black et al (1982) and modified as previously reported (Provencher et al, 1990). All the chemicals and culture media used for the preparation of FG cells have been described (Provencher et al, 1992c).…”
Section: Dna Extraction and Southern Blot Analysismentioning
confidence: 99%
“…The least-squares fit of the data points to a v against s hyperbola was used to calculate best-fit values of Vmax and Km, and results were reported as means ± SEM. Preparation of dispersed guinea pig fasciculatal glomerulosa cells Adult male guinea pigs (Hartley) weighing 850 grams were used for the preparation of primary cultures of fasciculata/glomerulosa (FG) cells, which were isolated using an adaptation of the procedure described by Black et al (1982) and modified as previously reported (Provencher et al, 1990). All the chemicals and culture media used for the preparation of FG cells have been described (Provencher et al, 1992c).…”
Section: Dna Extraction and Southern Blot Analysismentioning
confidence: 99%
“…Catalytic properties were carried in intact COS-I cells with HPLC-purified (7-3H)pregnenolone (0.36 mCi, 23.5 Wmmol), (1,2,6,7-3H)progesterone (0.36 mCi, 94 Ci/mmol), 17-hydroxy (7-3H)pregnenolone (0.36 mCi, 20 Ci/mmol), and 17-hydroxy (1,2,6,7-3H)progesterone (0.36 mCi, 65 Ci/mmol). The steroids were separated by TLC and determined by comigration on each TLC of an HPLC authentic labeled steroid.Prevaration of disversed guinea pip adrenal (GAC) cellsThe GAC were isolated using an adaptation of the Black et a1(13) procedure modified as reported(14). GAC were plated at 1.25 x 106 cells/ml Endocr Res Downloaded from informahealthcare.com by McMaster University on 11…”
mentioning
confidence: 99%
“…These cells retain their abundant SER in vitro, particularly in the presence of ACTH (74). Both CYP17 and Sec61were distributed fairly evenly throughout the tubular ER network of the isolated cells (Fig.…”
Section: Immunocytochemistrymentioning
confidence: 89%
“…Isolated adrenocortical cells were prepared and grown on coverslips, as previously described (74). After 3-5 d in culture, in the presence or absence of ACTH (100 mU/ml), the cells were rinsed briefly with PBS and fixed for 10 min on ice with methanol that had been stored at Ϫ20 C. Subsequent incubations were carried out at room temperature in 1% milk in PBS [blocking, 1 h; primary antibody (1:200), 1-5 h; three rinses; secondary antibody (fluorescein-conjugated AffiniPure F(abЈ)2 fragment donkey antirabbit IgG (HϩL), Jackson ImmunoResearch Laboratories Inc, West Grove PA)(1:125), 1 h], followed by several rinses in plain PBS.…”
Section: Immunocytochemistrymentioning
confidence: 99%